The Role of Systemic Enablers in Integrating Knowledge Management for Innovation - Firmansyah, Boy (Data : Journal of Information Systems and Management, 2024)
This narrative review explores the critical intersection between Knowledge Management (KM) practices and organizational innovation. As innovation becomes a key determinant of competitive advantage in the digital economy, organizations increasingly rely on KM strategies to harness collective expertise and accelerate problem-solving. The study synthesizes peer-reviewed literature drawn from Scopus, Web of Science, and Google Scholar using targeted keywords and Boolean combinations related to KM, innovation, and organizational learning. Inclusion criteria focused on empirical and theoretical studies that directly connect KM practices with innovation outcomes across diverse sectors and geographical settings. The results reveal that communities of practice, digital knowledge platforms, and strategic alignment of KM are primary drivers of innovation. Factors such as organizational culture, leadership style, and structural flexibility significantly mediate KM effectiveness. Cross-national comparisons highlight disparities in KM integration, with institutions in technologically advanced economies showing higher maturity levels. Challenges identified include resistance to change, underdeveloped digital infrastructure, and compartmentalized organizational silos. The discussion emphasizes policy and institutional strategies to overcome systemic constraints, including fostering leadership in KM and embedding KM within cross-functional collaboration initiatives. This review underscores the strategic importance of KM in enabling sustainable innovation and recommends future research on context-specific implementation and long-term impact. It calls for broader geographic representation and multi-sectoral analysis to develop more inclusive KM frameworks responsive to global innovation demands.